Bridge decks of fibre reinforced polymer (FRP): A sustainable solution - Mara, Valbona; Haghani, Reza; Harryson, Peter (Construction & building materials, 2014)
•FRP decks offer rapid erection, less negative impact on users and improved social sustainability.•Using FRP deck systems for refurbishment purposes offers less indirect costs.•Bridges with FRP deck are environmentally favourable in terms of low carbon emissions.•Polymer concrete is not a suitable option for wear surface in terms of environmental impacts. Fibre reinforced polymer (FRP) bridge decks have become an interesting alternative and they have attracted increasing attention for applications in the refurbishment of existing bridges and the construction of new bridges. The benefits brought by lightweight, high-strength FRP materials to these applications are well recognised. However, the sustainability of bridge concepts incorporating FRP decks still needs to be demonstrated and verified. The aim of this paper is to bridge this knowledge gap by examining the sustainability of these FRP solutions in comparison with traditional bridge concepts. An existing composite (steel–concrete) bridge with a concrete deck that had deteriorated was selected for this purpose. Two scenarios are studied and analysed; the total replacement of the entire bridge superstructure and the replacement of the concrete deck with a new deck made of GFRP. The analyses prove that FRP decks contribute to potential cost savings over the life cycle of bridges and a reduced environmental impact.